2014
DOI: 10.1152/physrev.00033.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acids in the Brain: Gangliosides and Polysialic Acid in Nervous System Development, Stability, Disease, and Regeneration

Abstract: Every cell in nature carries a rich surface coat of glycans, its glycocalyx, which constitutes the cell's interface with its environment. In eukaryotes, the glycocalyx is composed of glycolipids, glycoproteins, and proteoglycans, the compositions of which vary among different tissues and cell types. Many of the linear and branched glycans on cell surface glycoproteins and glycolipids of vertebrates are terminated with sialic acids, nine-carbon sugars with a carboxylic acid, a glycerol side-chain, and an N-acyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
604
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 630 publications
(615 citation statements)
references
References 567 publications
8
604
0
3
Order By: Relevance
“…Selective polysialylation determined by specific core residues has been reported for glycoproteins expressed in CHO cells (30). Nevertheless, others have shown that distinct types of glycans are not required for polyST activity (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Selective polysialylation determined by specific core residues has been reported for glycoproteins expressed in CHO cells (30). Nevertheless, others have shown that distinct types of glycans are not required for polyST activity (1).…”
Section: Discussionmentioning
confidence: 99%
“…These negatively charged sugar residues (i.e., N-acetylneuraminic acid) play essential roles in many aspects of life: e.g., in cell-cell interactions, in cell signaling, and for protein stability (1,2). A unique feature of Sia is that, unlike other sugars, it often forms homo-oligomers or polymers, with its most complex form polysialic acid (polySia) reaching a degree of polymerization up to 400 (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments in mice have shown that the interaction of myelin-associated glycoprotein (MAG) with gangliosides on the axon surface is essential for the stability of axonmyelin units (Schnaar, 2010;Schnaar et al, 2014). MAG is a sialic-acid-binding lectin (Siglec-4) with high specificity for N-acetylneuraminic acid (Neu5Ac) (Collins et al, 1997).…”
Section: Modeling the Cause Of The Primary Lesionmentioning
confidence: 99%